A single centre experience of prosthetic joint infection outcomes with outpatient parenteral antimicrobial therapy. Issue 4 (April 2023) - Kutubi, Abdubadie; O'Brien, Luke; Murphy, Ben; Fitzpatrick, Patricia; Hurson, Conor; Rajendran, Deepa; Feeney, Eoin; Mallon, Patrick; Waqas, Sarmad
Abstract: Objectives: Prosthetic joint infection (PJI) is a serious complication following arthroplasties. This study assessed the clinical outcomes, readmission rates and financial impact of PJIs treated with outpatient parenteral antimicrobial therapy (OPAT). Methods: The study used prospectively collected data from the OPAT patient database at a tertiary care Irish hospital for PJI cases managed between 2015 and 2020. Data was analyzed using IBM-SPSS. Results: Forty-one patients with PJIs were managed via OPAT over five years, with median age of 71.6 years. Median duration of OPAT was 32 days. Hospital readmission occurred in 34% of cases. Reasons for readmission included progression of infection in 64.3%, unplanned reoperation in 21.4% and planned admission for joint revision in 14.3%. Type 2 Diabetes Mellitus (T2DM) was found to have a statistically significant association with unplanned readmission (OR 8.5, CI 95% 1.1–67.6; p < 0.01). OPAT saved a mean of 27.49 hospital-bed days per patient. 1, 127 bed days were saved in total, estimating a total savings of 963, 585 euros and median savings of 26, 505 euros. Conclusions: The readmission rate observed was comparable to international data. Most readmissions were related to primary infections rather than due to OPAT-specific complications. Our main findings were that patients with PJIs can be safely managed via OPAT, and the finding of association between T2DM and increased risk of readmission. Highlights: OPAT is a safe and effective modality in the treatment of PJI. Type 2 Diabetes Mellitus is associated with an increased rate of readmission. There were significant financial benefits associated with the use of OPAT vs. inpatient antimicrobial therapy.